Implementation Of Occupational Safety And Health Management System At PT. Port Indonesia IV (Persero) Gorontalo Branch - Margaretha Husain; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Estudiante Law Journal, 2023)
Pelabuhan Indonesia IV (Persero) Gorontalo Branch is one of the State-Owned Enterprises engaged in Port Services, Ship Services, Goods Services, and Container Terminals. PT Pelabuhan Indonesia IV Gorontalo branch is also one of the companies in Gorontalo that implements an occupational safety and health system in the company's operational processes. The company needs to prepare facilities and infrastructure as well as programs that can minimize the number of work accidents in the company, preparations made to anticipate and reduce the number of work accidents caused by hazard factors and the risk of work accidents consist of hazard identification, assessment of potential hazards, organization and means of operational supervision of emergency action planning, dissemination of information to employees and the surrounding community regarding company actions in an effort to prevent the emergence of environmental pollution hazards generated by the company. ensure occupational safety and health in the company and reduce the risk of accidents in the work environment. Therefore, the Occupational Safety and Health Management System is very important for companies and workers to minimize the occurrence of work accidents in the work environment. We cannot underestimate all matters relating to work safety.